CARACTERIZACIÓN MORFOMÉTRICA Y FANERÓPTICA DE LA GALLINA CRIOLLA (Gallus gallus domesticus) EN EL CANTÓN VENTANAS, LOS RÍOS - Villasnay Ibarra, Emely Julissa (2023)
The ancestral origin of the domestic hen is from Southeast Asia, in Ecuador the raising of field birds is an important activity in developing rural communities. The objective of the research was: To determine the morphometric and phaneroptic characteristics of the Creole hen (Gallus gallus domesticus), in the Ventanas canton, Los Ríos province. 92 hens and 20 roosters where the total average weight of the sample was 1.90 ± 0.08 kg were evaluated. The descriptive analysis by sex showed a higher average weight in roosters with 2.42 ± 0.12 kg and lower weight in Creole hens with 1.79 ± 0.09 kg.